Sosialisasi Kampung Ramah Anak Usia Dini Di Desa Way Hui Lampung Selatan - Ari Sofia; Rizky Drupadi; Ulwan Syafrudin; Annisa Yulistia (Jurnal Pengabdian Pada Masyarakat, 2022)
This community service aims to provide assistance in creating the best urban environment for child development through community awareness. Activities carried out through several stages include ensuring the existence of a physically and socially strong community, the existence of a community that has clear and firm rules, the existence of a community that allows providing opportunities for children and ensuring educational facilities that provide opportunities for learning and their environment and world. . This socialization is motivated by the many findings in families (early children and their caregivers) around the world, especially those who live in poverty or in informal operations, need services that are more accessible, families face poor public transportation, unhealthy food, poor sanitation, insufficient health care, and a lack of affordable child care. These problems can hinder the intellectual development and personality of children. Therefore, it is necessary to plan and design family-centered urban areas, not only to build many playgrounds, but more than that, such as; public transportation, public facilities, health facilities, protection facilities, care, education and public spaces that are safe, clean, and free for small children and families to play together. The service was held in Way Hui Village, South Lampung with a total of 20 participants